RANCANG BANGUN PROTOTYPE PENJEMURAN BAJU APD PKP-PK BERBASIS ARDUINO UNO - Muhammad Aris Solihin; Supri Supri; Ika Endrawijaya (Informatika: Jurnal Teknik Informatika dan Multimedia, 2025)
The drying system for Personal Protective Equipment (PPE) in the Aircraft Rescue and Fire Fighting (PKP-PK) study program is essential to maintain hygiene and prevent mold growth due to storing damp equipment. To address this issue, a prototype of an automatic drying rack based on Arduino UNO was designed to operate according to weather conditions and clothing moisture levels. The system uses a rain sensor (FC-37), light sensor (LDR), and moisture sensor (YL-69) as input components, and a servo motor (Tower Pro SG90) to move the drying rack. Weather and clothing status information is displayed in real-time on an I2C 16x2 LCD. Test results show that the system can automatically and responsively adjust the drying rack's position based on sensor data, effectively aiding the PPE drying process while reducing the need for manual monitoring.